2017
DOI: 10.1186/s12881-017-0428-1
|View full text |Cite
|
Sign up to set email alerts
|

Two novel C-terminal frameshift mutations in the β-globin gene lead to rapid mRNA decay

Abstract: BackgroundThe thalassemia syndromes are classified according to the globin chain or chains whose production is affected. β-thalassemias are caused by point mutations or, more rarely, deletions or insertions of a few nucleotides in the β-globin gene or its immediate flanking sequences. These mutations interfere with the gene function either at the transcriptional, translational or posttranslational level.MethodsTwo cases of Polish patients with hereditary hemolytic anemia suspected of thalassemia were studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…In the last few years, it has become evident that mRNA stability/turnover provides an important mechanism for post-transcriptional control of gene expression [ 25 ]. Many studies have reported that frameshift variants can lead to disease by affecting the stability of mRNA [ 26 , 27 , 28 ]. Therefore, the p.S119Pfs*2 variant may lead to tooth agenesis by affecting the stability of mRNA, but the specific mechanism needs more experiments to verify.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, it has become evident that mRNA stability/turnover provides an important mechanism for post-transcriptional control of gene expression [ 25 ]. Many studies have reported that frameshift variants can lead to disease by affecting the stability of mRNA [ 26 , 27 , 28 ]. Therefore, the p.S119Pfs*2 variant may lead to tooth agenesis by affecting the stability of mRNA, but the specific mechanism needs more experiments to verify.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the majority of them are located between codons 109 and 141, and no corresponding Hb variants could be detected in peripheral blood of the patients. In fact, the dominant form of β-thalassaemia intermedia could be related to messenger RNA (mRNA) stability mechanisms 8. If the premature termination is located so early, for example, within exon 2, the corresponding transcript is targeted for nonsense-mediated mRNA decay (NMD), no protein is synthesised and heterozygotes are asymptomatic.…”
Section: Resultsmentioning
confidence: 99%
“…This deletion causes the loss of the third exon, therefore may produce a short unstable mRNA that could undergo early degradation. This early degradation mechanism is typical for mutations inducing a premature termination codon in coding sequences (Grosso et al, 2008;Rawa et al, 2017). It is important to notice the unusual increased HbF in the mother, who is a simple heterozygote for this deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Although single nucleotide mutations represent the vast majority of b-thalassemias, deletions involving HBB gene, or its regulating sequences have also been associated to this pathology (Patrinos GP et al, 2004). Despite being an autosomal recessive inherited condition, some forms of b-thal are inherited dominantly (b D alleles), so is the case of nonsense or frameshift mutations in exon three that result in the formation of a premature termination codon and therefore the production of unstable b-globin chains that precipitate along with the free a-globin chains in the erythroid precursor causing premature death and ineffective erythropoiesis (Thein, 2018;Rawa et al, 2017). b-thal is classified according to severity as minor, major and intermedia (Thein and Wood et al, 2009;Thein, 2018).…”
Section: Introductionmentioning
confidence: 99%